Electrostatic Field Effect Light-Emitting Diode - Matthew Hartensveld; Bryan Melanson; Jing Zhang (IEEE Photonics Journal)
Gallium Nitride (GaN) based light-emitting diodes (LEDs) suffer from the persistent issue of high resistivity of the p-type layer, due to inefficient dopant activation at room temperature. Here, a novel Electrostatic Field Effect LED (EFELED) is demonstrated to solve this issue by introducing significantly more holes into the LED active region for the first time. An increase in drive current is observed through application of positive biases to a capacitor layer on top of a 436 nm InGaN/GaN LED. With a positive bias of 5 V applied to the capacitor, the EFELED showed more than a two-fold increase in optical output from electroluminescence (EL) measurements, as well as over 115% enhanced external quantum efficiency (EQE). Modulation of holes can also be achieved through the novel capacitor integration in the EFELED, which leads to light output control. This proposed EFELED provides an alternative method to efficiently improve hole injection for the active region through energy band bending, which addresses the fundamental p-type doping issue for LED devices.